Youth mental health in the time of COVID-19. (2nd December 2020) - Power, E.; Hughes, S.; Cotter, D.; Cannon, M.
Abstract : Youth mental health is a rapidly developing field with a focus on prevention, early identification, treatment innovation and service development. In this perspective piece, we discuss the effects of COVID-19 on young people's mental health. The psychosocial effects of COVID-19 disproportionately affect young people. Both immediate and longer-term factors through which young people are affected include social isolation, changes to the delivery of therapeutic services and almost complete loss of all structured occupations (school, work and training) within this population group. Longer-term mechanisms include the effects of the predicted recession on young people's mental health. Opportunities within this crisis exist for service providers to scale up telehealth and digital services that may benefit service provision for young people's mental health in the future.